The Effect of Using the Trainchinese Dictionary on the Learning Outcomes of Chinese Students in Class X in High School - Dinda Ayuningtiyas, Edwien (Pusat Publikasi Nusantara, 2023)
Understanding Chinese is not just about the spoken word, but also the written word. Chinese has thousands of strokes that need to be understood, one of the oldest being the ?? (hànzi) strokes. In the scope of education, teaching ?? (hànzi) strokes and Chinese sentence construction is a challenge. The reason is that students have not found it easy to learn the material. The results of Chinese ?? (hànzi) strokes and sentence construction are the variables to be tested. Using a quantitative approach with an experimental nonequivalent control group design, this study involved 45 students who were divided into experimental and control groups. The results showed a significant improvement in the learning outcomes of the experimental group after being assisted with the Trainchinese digital dictionary